View of the Orthographic Peculiarities of the Arabic Alphabet in Bosnian Primer of Ibrahim Berbić - Kadrić, Adnan (Prilozi za orijentalnu filologiju, 2017)
According to thc information available to the author of this work. the orthographic adaptation of the Arabic alphabet for the needs of writing in Bosnian language, was especially intense in the second half of 19m century. Subject of this work are the orthographic peculiarities of the Arabic alphabet in Berbić's "Wit.h the Old and the New Alphabet to the Bosnian Primer" (Sa starom i novom jazijom bosanskoj clifnici"), issued in 1889, in Istanbul. The cmphasis is put especially on the transcription of nominal words (proper and common nouns, terms), verbs and certain forms of adjeetives. This vvork also gives a rcvievv of orthographic representation of words of Turkish origin, and the problems of different versions of their transmorphemization, i.e. their morphological adaptation to morphophonological system of Bosnian language. The conclusion reached in the basis of the information available to the author, and given in the final part of this work is that Berbić's Primer was certainly not the only one written in what was considered to be "a whole new way of writing" and a new alphabet. Such discoveries enlighten the theories of İbrahim Berbić, being the reformer and the innovator of Arabic alphabet in Bosnian language, and his origin, in a new and different way. What we can be certain of is that Berbić had used the version of Arabic alphabet described in this work.